Pengaruh Platform Jual Beli Online Terhadap Perilaku Konsumen Pada Perawat Rumah Sakit Bhayangkara Setukpa Polri - Sikki, Nurhaeni; Indriyani, Devi; Suwartika, Wawat; Maulana, Fajar; Solihin, Khoirul; Suarman, M Dani; Putra, Angga Tri Adi; Kristi, I Sildani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to analyze the influence of online shopping platforms on consumer behavior among employees of Rumah Sakit Bhayangkara Setukpa Polri. Using a quantitative approach, data were collected through questionnaires distributed to 100 employees as respondents. Data analysis was conducted using simple linear regression to identify the significant impact of online shopping platforms on purchasing decisions and shopping frequency. The results indicate that the use of online shopping platforms has a positive and significant effect on consumer behavior. These findings are expected to provide insights for hospital management in understanding the consumption trends of their employees.